Relation between serum xenobiotic induced receptor activities and DNA damage and sperm apoptotic markers in European and Inuit populations - Long M.; Stronati A.; Bizzaro D.; Kruger T.; Hjelmborg P. S.; Spano M.; Giwercman A.; Toft G.; Bonde J. P.; Bonefeld Jorgensen E. C.; MANICARDI, Gian Carlo (Toxicology Letters, 2008)
Persistent organic pollutants (POPs) can interfere with hormone activities and are suspected as endocrine disrupters involved in, e.g. reproductive disorders. We investigated the possible relation between the actual integrated serum xenoestrogenic, xenoandrogenic and aryl hydrocarbon receptor activities and the sperm DNA damage and sperm apoptotic markers of 262 adult males (54 Inuits from Greenland, 69 from Warsaw (Poland), 81 from Sweden and 58 from Kharkiv (Ukraine) exposed to different levels of POPs.